Criminalizing examination cheating: Surveillance, punishment and newspaper discourse - Othuon, Judith Akoth; Ngumo, Mugambi Cyrus; Omoke, Lillian Kemunto (Research Journal in Advanced Humanities, 2026)
Although there are considerable studies in Kenya on examination cheating, there is very limited focus on how the media discursively constructs the issue. To address this gap, this article, using Fairclough’s Critical Discourse Analysis (CDA) and Michel Foucault’s theory of disciplinary power, examines how Kenyan daily newspapers discursively construct examination cheating. Corpus was drawn from news and opinion articles, and their headlines published in the Daily Nation and The Standard between 2022 and 2024. Sampling followed a cyclic and iterative procedure until discursive saturation was reached. The analysis was complemented by corpus tools; AntConc (Version 4.3.1) to aid in finding frequencies, salient lexical and grammatical patterns and SKELL Engine to further support the analysis of collocations. The analysis reveals that examination cheating is dominantly constructed as a crime. Lexical patterns like collocation, metaphors and overwording link cheating with control, punishment and institutional authority. Grammatical choices foreground state institutions as powerful agents while backgrounding students, teachers, and parents, who are mainly represented as offenders or passive subjects. Institutional and elite voices dominate the discourse of examination cheating, while the voices of other actors are either marginalized, backgrounded or entirely silenced. Alternative perspectives that address structural pressures such as high-stakes testing and inequality are barely mentioned. Through intertextuality, legal, crime and economic discourses are recontextualized to reinforce the criminalization of examination cheating. The moral and ethical dimensions of examination cheating are also rarely explored. The study concludes that Kenyan newspaper discourse plays a central role in criminalizing examination cheating thereby legitimizing surveillance, normalization and punishment.